Analisis Dampak Kebijakan Fiskal: Evaluasi Perubahan Peraturan Pajak Tahun 2021 terhadap Pertumbuhan Ekonomi di Kalteng - Lausanne Dwi Nove Ompusunggu; Tanti M. Rajagukguk; Rifka Eliza Ambarita; Devy Sinta Sari; Nadia Anggreani; Nita Beti Lestari; Niat Niat; Yesaya Lala; Dicky Perwira Ompusunggu (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This study aims to evaluate how these changes in taxation policy affect the economic dynamics of the region. Through a quantitative approach and using secondary data from Statistics Indonesia, this research includes a Difference in Difference analysis to compare the changes in economic growth before and after the changes in tax regulations in Central Kalimantan. This evaluation is important because fiscal policy, especially in terms of taxation, has great potential to affect people's welfare, the region's competitiveness in attracting investment, as well as the growth of key sectors. The results will provide a deeper understanding of the implications of fiscal policy on the regional economy, provide valuable input for future policy decision makers, and serve as a guideline for other regions that may face similar policy changes.